Managing Health Services - Tight Integration or Loose Coupling? - Mervi Vähätalo; Tomi J. Kallio (Association of Business Schools Finland, 2022)
The extant modularity literature suggests two contradicting strategies—loose coupling and tight integration—for conducting supply chain management (SCM). This study analyzes how, in what circumstances, and for what purposes loose coupling and tight integration are applied in SCM within health and social services. The study is qualitative and exploratory. The analysis indicates four types of loose coupling, mainly related to purchasing and mostly applied in formal contracting to ensure lawfulness of service, and three types of tight integration, mainly applied in less formal projects to promote service effectiveness and add customer value. These SCM strategies support service delivery and do not exclude each other in the organization of health and social services. The study encourages health and social service managers to select the combination of SCM strategies that benefits all suppliers as well as end users of the services.